The Integration of Spirituality and Technology: The Role of Christian Education in the Digitalization Era - Naibaho, Dorlan; Widiastuti, Maria; Hasugian, Jessi Manuella; Nababan, Benida Dina (LP. Ma'arif Janggan Magetan, 2024)
The rapid development of digitalization has profoundly influenced students' spiritual lives, often shifting their patterns of worship, meaning-making, and social interaction. This study aims to explore the role of Christian education and worship learning in shaping student spirituality within the context of the digital era. Using a qualitative descriptive approach through library research, this study analyzes scientific books, theological journals, educational articles, and relevant research reports published in the last 15 years. The findings indicate that contextual, reflective, and experiential Christian education significantly contributes to holistic spiritual formation. Worship learning, when designed meaningfully, serves as a powerful medium to deepen faith experiences and initiate authentic spiritual transformation. In the digital era, students require digital spiritual literacy to ethically navigate information and use technology in ways aligned with their faith. The role of lecturers as spiritual mentors and the presence of an adaptive, value-based curriculum are critical in supporting students' spiritual development. The study concludes that Christian education remains highly relevant and increasingly urgent in an age where spiritual values are often marginalized. The implications of this research highlight the need to develop a Christian education curriculum that integrates faith and technology in critical and creative ways. Future research is encouraged to empirically examine the implementation of digital spiritual pedagogy and its long-term impact on student character and mission. This study contributes conceptually to the advancement of Christian education in higher education and offers a framework for developing resilient, reflective, and Christ-centered students in the digital age.